Biocontrol potential of Trichoderma spp. against important soilborne diseases of vegetable crops - KAPOOR*, A.S. (Indian Phytopathology, 2008)
In vitro studies on the efficacy of Trichoderma spp. against soilborne pathogens revealed maximum inhibition of mycelial growth by T. harzianum against Rhizoctonia solani, Pythium debaryanum, Sclerotinia minor and Fusarium oxysporum f. sp. pisi. Bioagent, T. viride showed maximum inhibition of mycelial growth of S. rolfsii. Similarly, the culture filtrate of T. harzianum showed maximum inhibition of mycelial growth of R. solani, Pythium debaryanum, S. minor, F. oxysporum f.sp. pisi and S. rolfsii. T. harzianum inhibited significantly the conidial germination of F. oxysporum f.sp. pisi and sclerotial germination of S. rolfsii as compared to other bioagents. Wheat bran alone or in combination with FYM in the ratio of 1:1 and 1:2 respectively supported maximum multiplication of T. harzianum followed by shelled maize cob powder, maize flour and FYM. Wheat bran based formulation as soil application @ 2 g/kg soil was found the best delivery system followed by seed treatment with same formulation @ 2g /kg seed or talc based formulation as seed treatment @ 2g/kg seed in controlling the root rot of pea and collar rot of tomato in pot experiments.